Bio-inspired fabrication of stimuli-responsive photonic crystals with hierarchical structures and their applications. (18th February 2016) - Lu, Tao; Peng, Wenhong; Zhu, Shenmin; Zhang, Di
Abstract: When the constitutive materials of photonic crystals (PCs) are stimuli-responsive, the resultant PCs exhibit optical properties that can be tuned by the stimuli. This can be exploited for promising applications in colour displays, biological and chemical sensors, inks and paints, and many optically active components. However, the preparation of the required photonic structures is the first issue to be solved. In the past two decades, approaches such as microfabrication and self-assembly have been developed to incorporate stimuli-responsive materials into existing periodic structures for the fabrication of PCs, either as the initial building blocks or as the surrounding matrix. Generally, the materials that respond to thermal, pH, chemical, optical, electrical, or magnetic stimuli are either soft or aggregate, which is why the manufacture of three-dimensional hierarchical photonic structures with responsive properties is a great challenge. Recently, inspired by biological PCs in nature which exhibit both flexible and responsive properties, researchers have developed various methods to synthesize metals and metal oxides with hierarchical structures by using a biological PC as the template. This review will focus on the recent developments in this field. In particular, PCs with biological hierarchical structures that can be tuned by external stimuli have recently been successfully fabricated. These findings offer innovative insights into the design of responsive PCs and should be of great importance for future applications of these materials.